Biotechnology and biodiversity debates and policies in Africa - Ayele, Seife (Inderscience Publishers, 2008)
After a decade of global diffusion, and the realisation of some economic benefits, the environmental impact of Genetically Modified (GM) crop technologies remains inconclusive and a source of considerable threat to biodiversity-rich Africa. Drawing on evidence from Ethiopia and South Africa, this paper characterises debates, considers policy and discusses the rationale for proactive GM technology policy (as in South Africa) and precautionary ones (such as in Ethiopia). It shows that GM crop adoption, or rejection, crucially depends on the scientific, technological and institutional capabilities for the development and use of the technology and perceptions about risk and socio-economic impacts. Overly protective policies (inadvertently) suppress the development of biotechnological capacities that have the potential to add more value to biodiversity-derived products, and reduce loss of biodiversity. It argues that Africa's progress in science and biotechnological innovation is central to conservation and sustainable use of its biodiversity for the improvement of the livelihoods of its people.